Synthesis and Characterization of Polymers Bearing Thiourea Moiety and Study Their Efficiency in Removing Heavy Metal Ions from Aqueous Solutions - Jaffer, Hamed Jasim; Reshan, Hawra`a Sarhan (Al-Nahrain Journal of Science, 2018)
Two new polymers were synthesized poly[5-amino-1,3,4-thiadiazol-2-yl (6-methanethioa- mido-6-oxohexanoyl)carbamodithioate] and Poly[N1-((6-aminopyridin-2-yl) carbamothioyl)-N6-thioformyladipamide]. These polymers were characterized by FTIR, 1H and 13C NMR spectra. These polymers were tested in removing some heavy metal ions (Cu(II), Cd(II), Zn(II), and Co(II)) from water. The adsorption behavior of these polymers has been studied using different parameters such as, contact time, initial metal ion concentration, weight of the polymer, pH of the solution and temperature. This study reveals that the two polymers have high adsorption capacity for mentioning metal ions. Langmuir, and Freundlich isotherm models were used to fit the experimental data. The experimental data of the adsorption equilibrium correlates well with the isotherm equations.